Comparative Study of Gas Ratio on Indium Nitride Thin Films Grown on Flexible Substrates Prepared by Reactive Sputtering Method - Osman, Siti Aisyah; Ng, Sha Shiong (2017)
In this report, indium nitride thin fi lms were deposited on kapton polyimide flexible substrate by reactive radio frequency (RF) sputtering method using an indium target in a mixture of Ar and N2 gases. The InN thin films were deposited under different gas ratio, i.e 90:10, 80 20, 70 30 and 6040 of N2 Ar The crystalline structures, surface morphologies, elemental composition and electrical properties of the deposited films were characterized by X-ray diffraction, field-emission scanning electron microscopy, atomic force microscopy, energy dispersive spectroscopy and hall effect The X-ray diffraction revealed wurtzite polycrystalline with hexagonal InN (002), (101), (102), (1 03) and (201) preferred growth orientation. The morphologies showed smooth and uniform surface of gas ratio at 6040 compare to others gas ratio. In overall, the characteristics of the InN thin films were effectively improved with combination the N2 Argas ration at 6040. The results showed that the gas ratio plays an important role in improving the properties of the InN thin films.